2016
DOI: 10.1016/j.addbeh.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Motives for marijuana use among heavy-using high school students: An analysis of structure and utility of the Comprehensive Marijuana Motives Questionnaire

Abstract: Motives for marijuana use are important predictors of problematic outcomes associated with marijuana use. Most measures, to date, were developed by adapting alcohol motives measures. However, the Comprehensive Marijuana Motives Questionnaire (CMMQ) was created using a bottom-up approach to evaluate twelve distinct motives for use. The CMMQ was developed and validated in a normative college population. As such, no known study has evaluated the factor structure and utility of the CMMQ in a heavy-using, high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
10
29
2
Order By: Relevance
“…Although many factors across levels of social ecology influence substance use (Abadi et al, 2011; Keyes et al, 2011; Sallis et al, 2008; Tang and Orwin, 2009), motives (i.e., reasons for use) are an important individual-level characteristic because they are related to negative consequences (Blevins et al, 2016b; Lee et al, 2009), including developing cannabis use disorders (Benschop et al, 2015; Schlossarek et al, 2016). Motives may change as a result of cannabis interventions; in prior work, reductions in motives (particularly coping-related motives) predicted post-intervention reductions in consumption and consequences (Blevins et al, 2016a), underscoring the need to examine how cannabis-related motives affect consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many factors across levels of social ecology influence substance use (Abadi et al, 2011; Keyes et al, 2011; Sallis et al, 2008; Tang and Orwin, 2009), motives (i.e., reasons for use) are an important individual-level characteristic because they are related to negative consequences (Blevins et al, 2016b; Lee et al, 2009), including developing cannabis use disorders (Benschop et al, 2015; Schlossarek et al, 2016). Motives may change as a result of cannabis interventions; in prior work, reductions in motives (particularly coping-related motives) predicted post-intervention reductions in consumption and consequences (Blevins et al, 2016a), underscoring the need to examine how cannabis-related motives affect consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Among college students who used cannabis at least once in the previous month, social, coping, expansion, and enhancement motives positively correlated with frequency of cannabis use over the month, whereas conformity was non-significant (Bravo et al, 2017). Using the expanded motives list among high school students using cannabis regularly, coping motives were positively related to externalizing (Blevins et al, 2016b) and higher coping, alcohol-related, and availability motives, along with lower celebration motives were associated with stronger internalizing (Blevins et al, 2016b). Among Dutch young adults using cannabis regularly, motives regarding routine use (i.e., boredom, habit) and coping were related to cannabis dependence (Benschop et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, items measuring the use of chemicals to reduce negative emotional states were found to be significant even after controlling for underlying psychiatric symptoms. Recent research by Blevins and colleagues (2016) on motives for marijuana use among heavy-using high school students revealed that using to cope with negative affect was more frequently endorsed by high school students compared to college students. Moreover, the tendency to use to cope was associated with more marijuana-related problems, lower self-efficacy for avoiding use, and higher rates of psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(85 – .91) and Availability (.69 – .89). For further information on the psychometric properties of the CMMQ in the present sample see Blevins and colleagues (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the CMMQ motive scales explained additional variance in use and consequences above and beyond the MMM in an initial study with college students (Lee et al, 2009). Confirmatory factor analysis of the CMMQ showed that the factor and subscale structure were replicated in much younger and more problematic population of cannabis users (Blevins et al, 2016). The present paper extends work on the clinical utility of the CMMQ by using the same sample of adolescent cannabis users to study change in motives following an intervention for cannabis use.…”
Section: Introductionmentioning
confidence: 99%